Small Island Developing States: between the concept and its application - Gallego Cosme, Mario (Journal of the Spanish Institute for Strategic Studies, 2021)
The concept of Small Island Developing State —or SIDS— was coined to categorize a group of States considered as a special group by the United Nations because of certain geographic and socioeconomic characteristics. It is a term that, in principle, seems to be self-explanatory by simply referring to the elements that compose its name. However, for various reasons, its application has been problematic, since there are some States which are considered to be SIDS in spite of not complying with some of the requirements that would follow from the term itself. By reviewing the elements that should be taken into account to justify a SIDS status, this essay invites to reflection on the current usefulness of the concept itself.
Keywords: Island States, Islands, SIDS, UN, UN-OHRLLS